Electroencephalographic (EEG) correlation of clinical Seizure among Bangladeshi Patients (Community Based Medical Journal, 2014)
To detect the changes in electro encephalogram (EEG) and correlate the findings with clinical seizure events among epilepsy patients. This retrospective chart review was carried out in the electrophysiology laboratory of Dhaka Medical College Hospital from January 2011 to December 2013, which included 1154 patients. EEG was obtained through scalp electrodes following international 10/20 system. Information regarding patients was collected from the laboratory register with the help of a checklist. The EEG findings and clinical seizure events were then compared. Among the 1154 patients, age varied from birth to 75 years. The mean age at presentation was 17±11.4 years and most of the patients were less than 10 years old (44.4%). The male (59.2%) female ratio was 3:2 in our study. Clinically diagnosed seizure was present in 970 patients (84.1%), among which Generalized tonic clonic seizure (GTCS) was the most common clinical type of seizure, followed by secondary generalized seizure in 19.4% (n=224) and focal seizure in 2% (n=30) patients and 6.8% (n=79) patients had pseudoseizure. Among the abnormal EEG (59%), generalized epileptiform discharge was found in 29%, whereas focal and secondary generalized discharge was found in 30%. The most common site of origin of epileptiform discharge was temporal lobe (28.3%). There was a negative correlation between EEG and history of seizure events (pearson correlation significance 0.33). Our study brings out the fact that EEG has a negative correlation with clinical seizure events.CBMJ 2014 July: Vol. 03 No. 02 P: 03-08